Synthesis, identification and in vitro biological evaluation of some novel quinoline incorporated 1, 3-thiazinan-4-one derivatives. Issue 3 (1st February 2017) - Umamatheswari, S.; Sankar, C.
Graphical abstract: Abstract: The present study describes the synthesis of two new series of 3-hydroxy- N -(4-oxo-2-phenyl-1, 3-thiazinan-3-yl)-8-(trifluoromethyl)quinoline-2-carboxamide derivatives (4a –j ) and 3-((7-chloroquinolin-4-ylamino)methyl)-2-phenyl-1, 3-thiazinan-4-one derivatives (5a –7j ). All the compounds were synthesized in moderate to good yield by one-pot three component cyclo-condensation reaction. The newly synthesized compounds were characterized by FT-IR, 1 H, 13 C NMR and elemental analysis. The compounds were screened for their in vitro antibacterial activity against a panel of pathogenic bacterial strains, antitubercular activity against Mycobacterium tuberculosis H37 Rv and also for their in vitro antimalarial activity against Plasmodium falciparum. Among the synthesized compounds two of them (4f and5f) showed excellent antibacterial activity against C. tetani at 15.6 μg/mL. Some of them exhibited excellent antitubercular (4f &5f ) and good antimalarial (4f, 5f &6f ) activity compared with the first line drugs.